Coronary Flow Evaluation in Heart Transplant Patients Compared to Healthy Controls Documents the Superiority of Coronary Flow Velocity Reserve Companion as Diagnostic and Prognostic Tool - Cecere, Annagrazia; Kerkhof, Peter L. M.; Civieri, Giovanni; Angelini, Annalisa; Gambino, Antonio; Fraiese, Angela; Bottio, Tomaso; Osto, Elena; Famoso, Giulia; Fedrigo, Marny; Giacomin, Enrico; Toscano, Giuseppe; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Distinct contributions by functional or structural alterations of coronary microcirculation in heart transplantation (HT) and their prognostic role have not been fully elucidated. We aimed to identify the mechanisms of coronary microvascular dysfunction (CMD) in HT and their prognostic implications. Methods 134 patients, surviving at least 5 years after HT, without evidence of angiographic vasculopathy or symptoms/signs of rejection were included. 50 healthy volunteers served as controls. All underwent the assessment of rest and hyperemic coronary diastolic peak flow velocity (DPVr and DPVh) and coronary flow velocity reserve (CFVR) and its inherent companion that is based on the adjusted quadratic mean: CCFVR = √{(DPVr)2 + (DPVh)2}. Additionally, basal and hyperemic coronary microvascular resistance (BMR and HMR) were estimated. Results Based on CFVR and DPVh, HT patients can be assigned to four endotypes: endotype 1, discordant with preserved CFVR (3.1 ± 0.4); endotype 2, concordant with preserved CFVR (3.4 ± 0.5); endotype 3, concordant with impaired CFVR (1.8 ± 0.3) and endotype 4, discordant with impaired CFVR (2.0 ± 0.2). Intriguingly, endotype 1 showed lower DPVr (p < 0.0001) and lower DPVh (p < 0.0001) than controls with lower CFVR (p < 0.0001) and lower CCFVR (p < 0.0001) than controls. Moreover, both BMR and HMR were higher in endotype 1 than in controls (p = 0.001 and p < 0.0001, respectively), suggesting structural microvascular remodeling. Conversely, endotype 2 was comparable to controls. A 13/32 (41%) patients in endotype 1 died in a follow up of 28 years and mortality rate was comparable to endotype 3 (14/31, 45%). However, CCFVR was < 80 cm/s in all 13 deaths of endotype 1 (characterized by preserved CFVR). At multivariable analysis, CMD, DPVh < 75 cm/s and CCFVR < 80 cm/s were independent predictors of mortality. The inclusion of CCFVR < 80 cm/s to models with clinical indicators of mortality better predicted survival, compared to only adding CMD or DPVh < 75 cm/s (p < 0.0001 and p = 0.03, respectively). Conclusion A normal CFVR could hide detection of microvasculopathy with high flow resistance and low flow velocities at rest. This microvasculopathy seems to be secondary to factors unrelated to HT (less rejections and more often diabetes). The combined use of CFVR and CCFVR provides more complete clinical and prognostic information on coronary microvasculopathy in HT.